O direito ao trabalho do preso como concretização do direito ao desenvolvimento : a necessidade de um regime jurídico específico - Carvalho, Gustavo Dantas (2017)
This dissertation, adopting the deductive method, aims to study the theoretical framework of the right to work of the incarcerated individuals, defending, initially, the fundamentality of such right as an expression of the fraternal stage of contemporary constitutionalism, as well as its enforceability towoards the State since, by depriving the individual of his freedom, he establishes with the condemned a special juridical relation, assuming the duty to give full effect to the rights of the prisoners, both as a way of guaranteeing their re-socialization, as well as implement the right to development that they hold, particularly because of their status as a socially vulnerable group. Finally, it's discussed the legal regime applied to the incarcerated work in a constitutional perspective, since the absence of normative discipline on the subject, as well as the inadequacy of the norms currently in force with the Federal Constitution of 1988, causes insufficient protection of the legal order to the right to work of the imprisoned.